Periportal fibrosis and other liver ultrasonography findings in vinyl chloride workers. Issue 1 (1st January 2003) - Maroni, M; Mocci, F; Visentin, S; Preti, G; Fanetti, A C
Abstract : Aims: To investigate the presence of liver lesions and their relation with vinyl chloride monomer (VCM) exposure or other personal risk factors, in workers involved in the production of VCM and polyvinyl chloride (PVC). Methods: A liver ultrasonography examination was conducted in 757 workers, some of whom had long standing service in the production of VCM and PVC. The study involved: assessment of individual past and present VCM exposure of each worker; collection of past personal health history, lifestyle and personal data; routine liver function tests; and liver ultrasonography. Results: No cases of liver malignancies were detected. Angiomas and liver cysts were found with a frequency of occurrence within the expected range of the general population. The main findings consisted of hepatomegaly (34.7%), steatosis (31.8%), and periportal fibrosis (16.0%). A logistic regression analysis indicated that hepatomegaly and steatosis were associated with obesity and lipid metabolism disturbances and not with VCM exposure. Periportal fibrosis, in addition to constitutional or dietary factors, was shown to be associated with VCM exposure, but only when maximum exposure in the subject's history had been at least 200 ppm as a yearly average; no effects were observed at 50 ppm or below. Conclusions: Workers exposed to 200 ppm VCM for at least one year have a fourfold increased risk of developing periportal liver fibrosis. Liver ultrasonography is a suitable and important diagnostic test for the medical surveillance of vinyl chloride workers.